1994
DOI: 10.1128/mcb.14.12.8391
|View full text |Cite
|
Sign up to set email alerts
|

The yeast type I topoisomerase Top3 interacts with Sgs1, a DNA helicase homolog: a potential eukaryotic reverse gyrase.

Abstract: We have previously shown that cells mutant for TOP3, a gene encoding a prokaryotic-like type I topoisomerase in Saccharomyces cerevisiae, display a pleiotropic phenotype including slow growth and genome instability. We identified a mutation, sgsl (slow growth suppressor), that suppresses both the growth defect and the increased genomic instability of top3 mutants. Here we report the independent isolation of the SGS1 gene in a screen for proteins that interact with Top3. DNA sequence analysis reveals that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
741
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 650 publications
(785 citation statements)
references
References 48 publications
43
741
0
1
Order By: Relevance
“…We therefore infer that Sgs1 helicase has a function in suppressing illegitimate recombination through the regulating formation of dicentric DNA molecules and thus the formation of double-strand breaks. Gangloff et al (1994) indicated that the frequency of intramolecular recombination between rDNA repeats is enhanced by the sgs1 mutation. Watt et al (1996) showed that the frequencies of interchromosomal homologous recombination, intrachromosomal excision recombination and ectopic recombination are enhanced by the sgs1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore infer that Sgs1 helicase has a function in suppressing illegitimate recombination through the regulating formation of dicentric DNA molecules and thus the formation of double-strand breaks. Gangloff et al (1994) indicated that the frequency of intramolecular recombination between rDNA repeats is enhanced by the sgs1 mutation. Watt et al (1996) showed that the frequencies of interchromosomal homologous recombination, intrachromosomal excision recombination and ectopic recombination are enhanced by the sgs1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Functional interaction between proteins involved in DNA replication, such as replication protein A (RPA) and DNA polymerase ␦, and WRN also have been reported (Shen et al, 1998;Brosh et al, 1999;Kamath-Loeb et al, 2000). Furthermore, in yeast, the RecQlike proteins seem involved in suppression of hyperrecombination, S-phase checkpoint control, and correct DNA segregation (Gangloff et al, 1994, Watt et al, 1995Stewart et al, 1997;Davey et al, 1998;Yamagata et al, 1998;Frei and Gasser, 2000). Noteworthy, yeast mutants in such RecQ-like helicases are extremely sensitive to agents that cause replication arrest, such as hydroxyurea because of uncontrolled illegitimate recombinational events (Stewart et al, 1997;Yamagata et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In budding yeast, a single RecQ member is encoded by the SGS1 gene. It is a 3 -5 DNA helicase (Bennett et al, 1998) interacting with topoisomerases Top3 and Top2 (Gangloff et al, 1994;Watt et al, 1995). Another ATP-dependent DNA helicase with 3 -5 polarity, playing a role in genome stability, is encoded by the MPH1 gene from Saccharomyces cerevisiae (Scheller et al, 2000;Prakash et al, 2005).…”
Section: Introductionmentioning
confidence: 99%